β-Glucan Subverts the Function of Myeloid Cells in Neonates - Yingying Chen; Hui Li; Lin Zhu; Quan Yang; Jie Zhou (Journal of Immunology Research)
β-Glucan is the main component of the cell wall of pathogen-associated molecular patterns (PAMPs) including various yeast, fungi, or certain bacteria. Previous reports demonstrated that β-glucan was widely investigated as a potent immunomodulators to stimulate innate and adaptive immune responses, which indicated that it could be recommended as an effective adjuvant in immunotherapy. However, the detailed effects of β-glucan on neonatal immunity are still largely unknown. Here, we found that β-glucan did not affect the frequencies and numbers of myeloid cells in the spleen and bone marrow from neonates. Functional assay revealed that β-glucan from neonates compromised the immunosuppressive function of immature myeloid cells, which were myeloid-derived suppressor cells (MDSCs). Flow cytometry or gene expression analysis revealed that β-glucan-derived polymorphonuclear (PMN)-MDSCs produced lower level of reactive oxygen species (ROS) and arginase-1 (Arg1) in neonatal mice. Furthermore, β-glucan administration significantly decreased the frequency and ROS level of PMN-MDSCs in vitro. These observations suggest that β-glucan facilitates the maturation of myeloid cells in early life, which may contribute to its beneficial effects against immune disorders later in life.